Efficacy and safety of teneligliptin added to metformin in Chinese patients with type 2 diabetes mellitus inadequately controlled with metformin: A phase 3, randomized, double‐blind, placebo‐controlled study. Issue 2 (20th January 2021) - Ji, Linong; Li, Ling; Ma, Jianhua; Li, Xuefeng; Li, Dongmei; Meng, Bangzhu; Lu, Weiping; Sun, Jiao; Liu, Yanmei; Takayanagi, Gen; Wang, Yi
Abstract: Introduction: We evaluated the efficacy and safety of teneligliptin compared with placebo when added to metformin therapy in Chinese patients with type 2 diabetes inadequately controlled with metformin monotherapy. Methods: This multicentre, randomized, double‐blind, placebo‐controlled, parallel‐group study enrolled type 2 diabetes patients with glycosylated haemoglobin (HbA1c) 7.0%−<10.0% and fasting plasma glucose (FPG) <270 mg/dl, receiving a stable metformin dose ≥1000 mg/day. Teneligliptin 20 mg or placebo was administered orally once daily (qd) before breakfast for 24 weeks. The primary efficacy end‐point was change in HbA1c from baseline to Week 24. Safety end‐points included the incidence of adverse events (AEs). Results: The least square mean (LSM) change from baseline (standard error [SE]) was −0.72 (0.07) (95% confidence intervals [CI], −0.87, −0.58) for teneligliptin and −0.01 (0.07) (95% CI, −0.16, 0.13) for placebo. The differences (LSM ± SE) between the placebo and teneligliptin groups in HbA1c and FPG were −0.71% ± 0.11% ( p  < .0001) and −16.5 ± 4.7 mg/dl ( p  = .0005), respectively. Teneligliptin yielded significant changes in HbA1c (−0.81%; p  < .0001) and FPG (−22.2 mg/dl; p  < .0001) at Week 12. At Week 24, more patients achieved HbA1c <7.0% with teneligliptin (41.7%) compared with placebo (16.1%; p  < .0001). Treatment‐emergent AE incidence was similar with teneligliptin (58.9%) and placebo (68.3%); upper respiratory tract infection, hyperuricaemia and hyperlipidaemia were the most common AEs. Conclusions: Teneligliptin 20 mg qd for 24 weeks added to ongoing metformin treatment significantly decreased HbA1c and FPG levels compared with placebo in Chinese type 2 diabetes patients. The combination was safe and tolerable. Abstract : In this multicenter, randomized, double‐blind, placebo‐controlled, parallel‐group study, we evaluated the efficacy and safety of teneligliptin compared with placebo when added to metformin therapy in Chinese patients with type 2 diabetes inadequately controlled with metformin monotherapy. Eligible type 2 diabetes patients receiving a stable metformin dose ≥1000 mg/day received teneligliptin 20 mg or placebo orally once daily (qd) before breakfast for 24 weeks to assess the primary efficacy end‐point (change in HbA1c from baseline to Week 24) and safety (including the incidence of adverse events). The least square mean (LSM) change from baseline (standard error [SE]) was −0.72 (0.07) for teneligliptin and −0.01 (0.07) for placebo, and the differences (LSM ± SE) between the placebo and teneligliptin groups in HbA1c and FPG were −0.71% ± 0.11% and −16.5 ± 4.7 mg/dl, with similar treatment‐emergent AE incidences in both groups, indicating that teneligliptin 20 mg qd for 24 weeks added to ongoing metformin treatment was safe and tolerable, and significantly decreased HbA1c and FPG levels compared with placebo in Chinese type 2 diabetes patients.